The Possible Ways to Empowering EFL Students’ Self-Confidence in Speaking Context - Prastowo, Fransiskus Regis Suluh Adiguna; Fiani, Ani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Speaking become one of the important skill among other skills in English learning. Speaking must be accompanied by good self-confidence, because it is important to convey the idea orally. However, EFL students feel not confident in English speaking. This study aim to find the ways to increase self-confidence in speaking context for EFL learners. In collecting data, researcher used literature study (Library Research) where library research is the activity of collecting materials related to scientific journals over past 5 years that are worthy of being used as sources for this research. After finish data collection from the journals, researcher analyzing qualitatively. The results of this study hopefully provide insights about how to increase EFL learners’ self-confidence in speaking context. Keywords: English, Self-Confidence, Speaking.